Type 2 Diabetes with Insulin Resistance Markers Fatty Liver Disease: A Biochemical Approach - abduljabbar m.hussein , Moamel; Jasim Mohammed , Rehab; Azeez Mohammed , Mahmoud (Pure Sciences International Journal of Kerbala, 2026)
This study examined the correlation between type 2 diabetes mellitus (T2DM), insulin resistance, and fatty liver disease (FLD) using biochemical assessment of 50 diabetic patients diagnosed with FLD in comparison to 40 healthy persons. The findings indicated a substantial elevation in HOMA-IR among the patients (16.25±12.75) relative to the control group (1.74±0.96; p<0.001), signifying an increase of nearly ninefold. The C-peptide level was significantly enhanced in the patients (3.88±2.70) compared to the control group (2.64±1.02; p<0.001), and insulin levels were nearly 3.5 times more (31.61±21.53 vs. 8.70±5.16; p=0.007). Concerning hepatic functioning, patients exhibited markedly elevated levels of AST (37.00±19.34 vs. 22.53±5.11; p<0.001) and ALT (41.84±22.48 vs. 24.63±7.29; p<0.001), signifying hepatocellular injury, although ALP levels did not demonstrate a significant difference (110.70±45.97 vs. 104.20±22.08; p=0.414). A modest yet statistically significant reduction in albumin levels was noted (4.27±0.58 vs. 4.41±0.30; p=0.001). The HbA1c level in patients was considerably elevated at 8.24±1.28 compared to the control group at 4.93±0.47 (p<0.001), reflecting inadequate blood sugar regulation and a level about 67% greater in the diabetes-FLD cohort. Clinically, 78% of individuals had non-alcoholic fatty liver disease (NAFLD), whereas 22% presented with alcoholic fatty liver disease, underscoring the prevalence of NAFLD among diabetes patients.